Answer:
x = ± [tex]\sqrt{2}[/tex] , x = ± i
Step-by-step explanation:
f(x) = [tex]x^{4}[/tex] - x² - 2
to find the zeros , equate f(x) to zero , that is
[tex]x^{4}[/tex] - x² - 2 = 0
using the substitution u = x² , then
u² - u - 2 = 0 ← in standard form
(u - 2)(u + 1) = 0 ← in factored form
equate each factor to zero and solve for u
u - 2 = 0 ⇒ u = 2
u + 1 = 0 ⇒ u = - 1
convert u back into terms of x
x² = 2 ( take square root of both sides )
x = ± [tex]\sqrt{2}[/tex]
x² = - 1 ( take square root of both sides )
x = ± [tex]\sqrt{-1}[/tex] = ± i